High-Density Mapping of an Adult-Plant Stripe Rust Resistance Gene YrBai in Wheat Landrace Baidatou Using the Whole Genome DArTseq and SNP Analysis - Li, Qiang; Guo, Juan; Chao, Kaixiang; Yang, Jinye; Yue, Weiyun; Ma, Dongfang; Wang, Baotong (Frontiers in Plant Science, 2018)
Stripe rust, caused by the biotrophic fungus Puccinia striiformis f. sp. tritici (Pst), is one of the most widespread and destructive wheat diseases worldwide. Growing resistant cultivars is an effective approach for controlling this disease. However, because host resistance genes were easily overcome by new virulent Pst races, there is a continuous demand for identifying new effective wheat stripe rust resistance genes and develop closely linked markers for marker-assisted selection (MAS). Baidatou, an old Chinese wheat landrace, has been grown for several decades in Longnan region, Gansu Province, where stripe rust epidemics are frequent and severe. In our previous study, a single dominant gene YrBai in Baidatou was identified to control the adult-plant resistance (APR) to Chinese prevalent Pst race CYR33. And the gene was located on wheat chromosome 6DS by four polymorphic simple sequence repeat (SSR) and two sequence-related amplified polymorphism (SRAP) markers, with the genetic distances of two closely linked markers 3.6 and 5.4 cM, respectively. To further confirm the APR gene in Baidatou and construct the high-density map for the resistance gene, adult plants of F1, F2, F3, and F5:6 populations derived from the cross Mingxian169/Baidatou and two parents were inoculated with CYR33 at Yangling field, Shaanxi Province during 2014-2015, 2015-2016, and 2016-2017 crop seasons, respectively. The field evaluation results indicated that a single dominant gene confers the APR to Pst race CYR33 in Baidatou. 92 F3 lines and parents were sequenced using DArTseq technology based on wheat GBS1.0 platform, and 31 genetic maps consisted of 2,131 polymorphic SilicoDArT and 952 SNP markers spanning 4,293.94 cM were constructed. Using polymorphic SilicoDArT, SNP markers and infection types data of F3 lines, the gene YrBai was further located in 0.8 cM region on wheat chromosome 6D. These closely linked markers developed in this study should be useful for MAS for Baidatou in crop improvement and map-based clone this gene.